The Effect of Progressive Muscle Relaxation Towards Reducing Anxiety in Seventh Grade Students in Facing Exams at Islamic Boarding School of Al-Ikhlas Female Kuningan Jawa Barat - Rahmawati, Rika; Alfiani, Fitri; Arisanty Latifah, Riza (Ann Publisher, 2023)
Exams are one of the factors that affect the level of anxiety. The anxiety experienced by women higher than that of men, the reason is because the hormones possessed by women are faster in bringing out the side of empathy. One of them is facing an exam. Therefore, it is necessary to have an intervention to reduce anxiety, one of which is Progressive Muscle Relaxation therapy. This study aims to determine the effect of Progressive Muscle Relaxation to reduce anxiety levels in seventh grade students in facing exams. This quasi-experimental research uses a one group pretest-posttest design. The sample in this study amounted to 28 participants. The sampling technique used was total sampling. The research instrument using an anxiety questionnaire is the Hamilton Anxiety Rating Scale (HARS). This questionnaire has been tested for validity and reliability with a coefficient value of Cronbach's Alpha 0.793 with a total of 14 items. The data were analyzed using the Wilcoxon test to determine the effect of Progressive Muscle Relaxation on reducing anxiety levels. The results showed that there was a significant decrease in the results of the pre and post anxiety level questionnaires with an average decreasing value of 14.50. And the obtained Wilcoxon test results 0.000 < 0.05, which means that there is an effect of giving progressive muscle relaxation therapy on anxiety in class VII students. Progressive Muscle Relaxation can reduce anxiety levels in female students in facing exams.